2019
DOI: 10.1007/s40430-019-2024-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of flame propagation and performance of obstructed pulse detonation engine with variation of hydrogen and air

Abstract: Pulse detonation engine is a new technique of supersonic wave propagation and stands for high impulsive thrust. The objective of the present investigation is to analyze the detonation wave characteristic of a hydrogen-air mixture in the pulse detonation engine (PDE) having obstacles of blockage ratio 0.5. The three-dimensional reactive Navier-Stokes equations with realizable k − ɛ turbulence model are used to simulate the propagation of combustion flame. The reaction rate of excess hydrogen and excess air is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…They found that Schelkin spiral accelerate the flame propagation. Alam et al [63] numerically studied on flame propagation in obstructed pulse detonation combustor with hydrogen-air mixture. They found that performance is increase up to 4.46% and this value increase for 𝜙 = 1.3.…”
Section: Results From Cfd Simulation and Calorimetric Analysismentioning
confidence: 99%
“…They found that Schelkin spiral accelerate the flame propagation. Alam et al [63] numerically studied on flame propagation in obstructed pulse detonation combustor with hydrogen-air mixture. They found that performance is increase up to 4.46% and this value increase for 𝜙 = 1.3.…”
Section: Results From Cfd Simulation and Calorimetric Analysismentioning
confidence: 99%
“…In literature, many studies include ignition and DDT processes for the propagation of the detonation wave in the pulse detonation engines. Obstacle [14][15][16][17][18][19][20][21][22] and Shchelkin sphiral [23][24][25][26][27] are used as DDT mechanisms. In numerical studies on the flame's transition into a detonation wave, the filling stage is not included, and the fuel-oxidizer mixture is defined as premixed in the detonation tube.…”
Section: Introductionmentioning
confidence: 99%
“…In numerical studies on the flame's transition into a detonation wave, the filling stage is not included, and the fuel-oxidizer mixture is defined as premixed in the detonation tube. Alam et al [14] investigated the effects of different equivalence ratios on the DDT transition step and the detonation wave propagation using a pulse detonation engine configuration modeled with obstacles having a 0.5 blockage ratio. Tangirala et al [17] utilized ideal and benchmark tube pulse detonation engine configurations in their numerical studies, examining the DDT and blowdown stages in experimental work.…”
Section: Introductionmentioning
confidence: 99%